Cities and Regional Thought in Argentina and Chile Between 1850 and 1930 - Hardoy, Jorge; Langdon, María (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
This paper is a discussion of how scholars and government leaders in Argentina and Chile regarded four related aspects of regional and urban development: settlement, urban-rural imbalances, urban primacy and imbalances between centre and periphery, and the stark reality of social inequalities. Their analyses and their solutions are still valid today.